Exploring the expression profile of vitamin D receptor and its related long non-coding RNAs in patients with acute lymphoblastic leukemia - Norouzi,Akram (2021)
SUMMARY OBJECTIVE: Acute lymphoblastic leukemia (ALL) is the most common type of childhood cancer. Previous studies have indicated the involvement of vitamin D receptor (VDR) and related long noncoding RNAs (lncRNAs) signaling in the pathophysiology of several cancers. However, their contribution to ALL remains to be elucidated. METHODS: In this case-control study, 30 patients with newly diagnosed ALL and 30 age- and sex-matched healthy children were selected. Then, the level of 25(OH) vitamin D and the expression of VDR and four VDR-related lncRNAs were assessed. RESULTS: No significant difference in serum 25(OH) vitamin D was observed between patients with ALL (20.42±6.5 ng/mL) and healthy subjects (25.45±11 ng/mL). In addition, the expression of MALAT-1, HOTAIR, and P-21 was not statistically significant between the two groups. However, a significant reduction in VDR and H19 expression was observed in patients with ALL (p<0.05). CONCLUSIONS: 25(OH) vitamin D insufficiency was evident in both groups. VDR and H19 signaling might be contributed to the pathogenesis of ALL, which needs further investigations.